Respuesta :

g(−3)=2

g(0) = 3g(0)=3

Step-by-step explanation:

Given

The attached graph

Required

Determine

g(-3)g(−3)

g(x) = 3g(x)=3

Since a graph has been provided, the question will be solved graphically;

Solving g(-3)

This implies that;

x = -3

And the interpretation is to solve for the y value when x = -3

From the attached graph;

When x = -3; y = 2

Hence;

g(-3) = 2g(−3)=2

Solving g(x) = 3

This implies that;

y = 3

And the interpretation is to solve for the x value when y = 3

From the attached graph;

When y = 3; x = 0